2018
DOI: 10.1371/journal.pone.0195206
|View full text |Cite
|
Sign up to set email alerts
|

Production of xylitol and bio-detoxification of cocoa pod husk hemicellulose hydrolysate by Candida boidinii XM02G

Abstract: The use of cocoa pod husk hemicellulose hydrolysate (CPHHH) was evaluated for the production of xylitol by Candida boidinii XM02G yeast isolated from soil of cocoa-growing areas and decaying bark, as an alternative means of reusing this type of waste. Xylitol was obtained in concentrations of 11.34 g.L-1, corresponding to a yield (Yp/s) of 0.52 g.g-1 with a fermentation efficiency (ε) of 56.6%. The yeast was tolerant to inhibitor compounds present in CPHHH without detoxification in different concentration fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Moreover, high reductions were also achieved in furans and formic acid (100% HMF, 69% furfural, and 80% formic acid). A high efficiency of ion-exchange resin detoxification to remove acetic acid and phenolic compounds was also observed in the detoxification of hydrolysates from rapeseed straw [19], cocoa pod husk [17], and corn cob [27].…”
Section: Eop Hydrolysate Composition and Detoxificationmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, high reductions were also achieved in furans and formic acid (100% HMF, 69% furfural, and 80% formic acid). A high efficiency of ion-exchange resin detoxification to remove acetic acid and phenolic compounds was also observed in the detoxification of hydrolysates from rapeseed straw [19], cocoa pod husk [17], and corn cob [27].…”
Section: Eop Hydrolysate Composition and Detoxificationmentioning
confidence: 78%
“…In order to decrease the inhibitor compound concentrations in the acid hydrolysate, different detoxification methods were tested prior to fermentation assays. C. boidinii was the yeast used in the fermentation, which is considered one of the best microorganism producers of xylitol [17]. Fermentation tests, using synthetic media instead of hydrolysate, were conducted to determine the maximum xylitol yield and effect of glucose in the fermentation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Detoxified, 1.25% sulfuric acid hydrolysates (125 • C, 30 min) of chestnut shells (35.9% cellulose, 20% hemicellulose and 42.6% lignin) supported lower xylitol levels and yields by C. tropicalis cells over a longer fermentation period than observed when the yeast cells were grown on dilute acid hydrolysates of banana and water hyacinth leaves [35]. Xylitol production by Candida boidinii on cocoa pod husk (30.8% cellulose, 21.2% hemicellulose and 25.6% lignin) acid hydrolysate (120 • C) was observed, although an extensive length of fermentation time was required [36]. A number of investigations have explored the use of corncob (35% cellulose, 25% hemicellulose and 23% lignin) hydrolysates to support xylitol production by a variety of C. tropicalis strains [37][38][39][40][41][42][43].…”
Section: Xylitol Production By Candida Species From Agricultural Residuesmentioning
confidence: 84%
“…The weight of the pod husk reported in some clones can become an economic and environmental problem if it is not managed properly. Therefore, research has been carried out to establish the potential of this by-product; several authors have found that compounds such as pectins for pharmaceutical use (Adi-Dako et al, 2018), the fermentation product xylitol (Santana et al, 2018), and skincare gels (Abdul et al, 2016) can be obtained from pod husks. Hence, the large weight of the pod husk can be an advantage if it is used as raw material for other industries that generate products with high added value.…”
Section: Weight Of Fruit Parts and Number Of Seedsmentioning
confidence: 99%